Is the presence of AA amyloidosis associated with impaired coronary flow reserve?. (August 2016) - Bulut, Mustafa; Keles, Nursen; Caliskan, Zuhal; Kostek, Osman; Aksu, Feyza; Ozdil, Kamil; Akcakoyun, Mustafa; Demircioglu, Kenan; Yilmaz, Yusuf; Kanbay, Mehmet; Caliskan, Mustafa
Abstract: Background and aims: Systemic amyloid A protein (AA) amyloidosis may occur as a complication of many chronic inflammatory disorders. Patients receiving inadequate anti-inflammatory and immunosuppressive therapies have an increased risk of developing systemic AA amyloidosis. Inflammation plays a role in all stages and the thrombotic complications of atherosclerosis. In the absence of epicardial coronary stenosis, coronary flow reserve (CFR) reflects coronary microvascular dysfunction. In the present study, we hypothesized that amyloid advanced subclinical inflammation in chronic inflammatory diseases (CID) patients may further affect coronary microcirculation. Methods: Thirty-two patients with biopsy-diagnosed renal AA, 73 patients with non-amyloid CID, and a group of healthy volunteers were included in the study. The measurements of coronary flow velocity were performed by a single investigator with expertise in transthoracic Doppler harmonic echocardiography (TTDE). Results: The AA amyloidosis subgroup had significantly lower CFR values than other non-amyloid CID patients and the control individuals (1.8 (1.5–2.1) vs. 2.1 (2.0–2.4) and 3.0 (2.8–3.2), p  < 0.001). Multivariate logistic regression analysis indicated that the presence of AA amyloidosis and elevated hs – CRP independently predict impairment of the CFR ( p  < 0.05). Conclusions: The presence of AA amyloidosis is related to decreased CFR values and the presence of AA amyloidosis and elevated hs – CRP independently predict impairment of the CFR. Therefore, patients with AA amyloidosis may have an increased risk of developing coronary artery diseases. Highlights: Left ventricular diastolic parameters were significantly impaired in patients with AA amyloidosis. CFR of patients with AA amyloidosis were significantly lower than the patients with CID and normal population. Multivariate logistic regression analysis proved that presence of AA amyloidosis and elevated hs– CRP predict impaired CFR. The impaired CFR is associated with endothelial dysfunction and increased atherosclerosis risk. The AA amyloidosis patients may have increased risk of cardiovascular diseases compared to CID patients and control group.